My journey to the stars - Kelly, Scott, 1964-; Easton, Emily (Step into reading., 2019)
"Scott wasn't sure what he wanted to be when he grew up. He struggled in school and often got in trouble with his twin brother, Mark. Then one day Scott discovered a book about test pilots and astronauts that set him on a new path. His new focus led him to fly higher and higher, becoming first a pilot and then an astronaut, along with his brother--the first twin astronauts in history. But his greatest accomplishment of all was commanding the International Space Station and spending nearly a year in space, which set the record for the longest spaceflight by an American. This story of an ordinary boy who grew up to do extraordinary things will amaze and inspire young readers"--Provided by publisher.